Development of Student Worksheets Based on Contextual Teaching and Learning in Ecosystem Learning Materials - Annisa Ayu; Nirwana Anas (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to develop teaching materials in the form of Student Worksheets based on Contextual Teaching and Learning in Biology learning that are valid, practical, and effective in Ecosystem material. This type of research is research and development using the 4D model, namely, Define, Design, Develop, Disseminate. This research was conducted at SMA Muhammdiyah O9 Kualuh Hulu for the 2022/2023 academic year. The data were collected by using validation sheet, students response, and test instruments. Furthermore, data analyzed descriptively by using percentage and n-gain formula. The product stated valid by media (86%) and material (89%) validators. The practicality analysis result shows that the product developed very practical to use for facilitating students learning outcomes. The N-Gain results in this study obtained a value of 0.84 in the High category. Based on the current study finding, it can be concluded that the student worksheets based on contextual teaching and learning develoved were valid, practical, and effective to facilitate students’ learning outcomes in ecosystem learning material.